System Design for Ordering and Digitizing Website-Based Bus Tickets - Sari, Indah Purnama; Al-Khowarizmi, Al-Khowarizmi; Sulaiman, Oris Krianto; Apdilah, Dicky; Fachrizal, Ferry (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2024)
In the business world, generally users and company owners need something innovative to help support performance and make it easier to use or search for product data. The presence of this website-based internet will make it easier for all groups to be able to access all forms of information, including utilizing this media to be able to connect relationships between customers and the company's products, one of which is ordering bus tickets. Based on the various conveniences and uses that the internet has, a "Use of Information Systems in Ordering and Digitizing Website-Based Bus Tickets" was developed. This system was created with PHP, MySQL and Bootstrap software. This information system is designed to provide convenience in terms of ticket ordering services and obtaining other information needed by custome.